Otomasi Perencanaan Produksi pada Pondok Pesantren - Rahmasari, S A; Juliasari, A; Febryanto, W K (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Production planning is very necessary in a business process that aims to minimize the total cost of production. In this research, automation of production planning using data based on the Islamic boarding school business processes. This research uses descriptive research which aims to obtain information in the implementation of the business process planning of Islamic boarding school. The calculation of production costs in this study was carried out in Microsoft Excel by determining the total targets and raw materials of the Islamic boarding school business process, then calculating the production costs of the Islamic boarding school process until finding the optimal production costs for each student for 3 years. - The year of study is Rp. 1,242,542 rupiah / Islamic student for a total of 300 Islamic students.